Stretchable organic optoelectronic devices: Design of materials, structures, and applications - Lee, Hanbee; Jiang, Zhi; Yokota, Tomoyuki; Fukuda, Kenjiro; Park, Sungjun; Someya, Takao (Materials Science and Engineering R: Reports, 2021)
Mechanically stretchable optoelectronic devices have provided unprecedented advantages for modern society, with the development of the Internet of Things. Stretchable organic optoelectronic devices have recently emerged as promising candidates for next-generation human-friendly wearable devices and sensors. The combination of facile and cost-effective processing accessibility has triggered the rapid development of stretchable electronic materials and devices. This review presents some recent advances and remaining challenges in the field of stretchable organic optoelectronics. Specifically, it focuses on advanced approaches, including appropriate material selection and structure engineering, to build stretchable optoelectronic devices while also preserving their photonic/electrical performances under external mechanical stresses. In addition, the potential challenges and their corresponding response strategies are discussed for further development of functional devices. We anticipate that this review will inspire more studies that assist in expanding the practical applications and potential of stretchable optoelectronic devices in wearables, primary healthcare, and medical and humanoid systems.
Keywords: Appropriate materials; Functional devices; Mechanical stress; Organic optoelectronics; Primary healthcare; Response strategies; Stretchable electronics; Structure engineering; Mechanical conformability; Organic electronics; Stretchable materials; Stretchable optoelectronic devices